2017
DOI: 10.1111/tbed.12649
|View full text |Cite
|
Sign up to set email alerts
|

Source-receptor probability of atmospheric long-distance dispersal of viruses to Israel from the eastern Mediterranean area

Abstract: Summary Viruses that affect the health of humans and farm animals can spread over long distances via atmospheric mechanisms. The phenomenon of atmospheric long‐distance dispersal (LDD) is associated with severe consequences because it may introduce pathogens into new areas. The introduction of new pathogens to Israel was attributed to LDD events numerous times. This provided the motivation for this study which is aimed to identify all the locations in the eastern Mediterranean that may serve as sources for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This approach is reasonable as LSD is believed to be transmitted mainly by blood‐feeding arthropods and, therefore, political barriers such as country boundaries are not efficient to stop the spread of the disease. Nevertheless, some long distance jumps have occurred due to human‐mediated transportation of cattle between farms, regions, or countries, and even by wind transmission (Klausner, Klement, & Fattal, ; Mercier et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is reasonable as LSD is believed to be transmitted mainly by blood‐feeding arthropods and, therefore, political barriers such as country boundaries are not efficient to stop the spread of the disease. Nevertheless, some long distance jumps have occurred due to human‐mediated transportation of cattle between farms, regions, or countries, and even by wind transmission (Klausner, Klement, & Fattal, ; Mercier et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Following its emergence in Wuhan, cases of COVID-19 were exported outside of China, mainly by travelers using the global aviation networks (Wu et al, 2020). It should be noted that transboundary spread of viruses is quite common in veterinary medicine ( Klausner et al, 2015 , Klausner et al, 2017 , Klausner et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that the length of the seasons has substantial influence on human and animal health. For instance, multi‐annual predictions of seasonal respiratory viruses were improved using the annual periodicity of the seasons and synoptic‐scale parameters (Yaari et al, ; Axelsen et al, ; Klausner et al, ; Zhao et al, ). These viruses have become a source of considerable human and animal morbidity and mortality (Cox and Subbarao, ; Peretz et al, ).…”
Section: Introductionmentioning
confidence: 99%